Development of an Immersive Educational Tool for Solar System Topics - Awanis Hidayati; Ani Susanti; Aji Wicaksono; Novaria Nusantara; Rieky Martin (SEAMEO SEAMOLEC, 2024)
The study of the solar system is a critical component of science education, offering students a deeper understanding of natural phenomena. However, traditional teaching methods often fall short in effectively engaging students and fostering comprehensive understanding. This study aims to develop an immersive learning tool utilizing metaverse technology, following the ADDIE development model. The resulting product includes two virtual spaces designed for exploration and learning by students. The evaluation process involved both Alpha and Beta Testing. Alpha Testing was conducted with four experts, comprising two specialists in AR, VR, and XR media, and two experts in science content. Beta Testing involved a small group of 15 students to assess the usability of the immersive application. The evaluation by media experts rated the learning tool as